EKSTRAKSI DAN PENENTUAN GUGUS FUNGSI ASAM HUMAT DARI PUPUK KOTORAN SAPI - Nurlina Nurlina; Intan Syahbanu; Mirna Tersiana Tamnasi; Chyntia Nabela; Maria Desi Furnata (Tanjungpura University, 2018)
Cow manure fertilizer was used as raw material for the extraction of humic acid in this research. The aim of this research were extraction of humic acid from cow manure fertilizer, characterization of functional groups based on FTIR spectra, and determination of humic acid functional groups. Humic acid extraction from cow manure used 0.050 M; 0.100 M; 0.250 M dan 0.500 M KOH solution. A cow manure fertilizer were shaken with KOH solution for 1; 2; 4 and 6 h. The quantitative determination of oxygen-containing functional groups of humic acid was conducted by titrimetri. The FTIR spectrum showed the presence of –OH group and N-H stretching (bands 3361.46 cm-1); C-H aliphatic for CH2, CH3 (2946.52 cm-1 and 1442.24 cm-1); C=C aromatic components (1626.48 cm-1); COO- symmetric stretching (1521.71 cm-1); C-O stretching from –COOH (1229.74 cm-1). Total acidity value was 500 cmole.kg-1 (Baryta Absorption Method); carboxyl groups content was 250 cmole.kg-1 (Ca-Acetate Method); and phenol (OH) concentration was 250 cmole.kg-1. It can be concluded that humic acid successfully extracted from cow manure fertilizer using 0.250 KOH solution as extractant for 2 h, which has yield of 4.486% humic acid.